The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/bdr2.1943
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exposure to hydroxychloroquine and birth defects

Abstract: Background Hydroxychloroquine is a treatment for rheumatic disease and considered safe during pregnancy. Interest in hydroxychloroquine has increased as it is being examined as a potential treatment and prophylaxis for coronavirus disease 2019. Data on the risks of specific birth defects associated with hydroxychloroquine use are sparse. Methods Using data from two case–control studies (National Birth Defects Prevention Study and Slone Epidemiology Center Birth Defects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…With regards to safety of HCQ in pregnancy, studies from the literature have suggested no hydroxychloroquine-related adverse effects on the fetus [ 20 , 50 , 61 , 62 , 63 , 64 , 65 ], with the exception of one meta-analysis that showed an increased rate of spontaneous pregnancy when HCQ was administered in the first weeks of pregnancy [ 66 ]. However, underlying conditions were not excluded when doing the meta-analysis, and therefore the result was potentially biased and thus further research is needed to provide accurate information.…”
Section: Results and Discussion: Hydroxychloroquine In Pregnancymentioning
confidence: 99%
“…With regards to safety of HCQ in pregnancy, studies from the literature have suggested no hydroxychloroquine-related adverse effects on the fetus [ 20 , 50 , 61 , 62 , 63 , 64 , 65 ], with the exception of one meta-analysis that showed an increased rate of spontaneous pregnancy when HCQ was administered in the first weeks of pregnancy [ 66 ]. However, underlying conditions were not excluded when doing the meta-analysis, and therefore the result was potentially biased and thus further research is needed to provide accurate information.…”
Section: Results and Discussion: Hydroxychloroquine In Pregnancymentioning
confidence: 99%
“…First, the sample size available for this analysis was insufficiently powered to rule out elevated risks for most specific individual major birth defects. However, specific patterns of major structural birth defects are characteristic of known human teratogens (28). Therefore, it is reassuring that no such pattern was identified in this study.…”
Section: Discussionmentioning
confidence: 99%